Alternative clay bricks inspired from termite mound biomimicry. (June 2022) - Sanga, Reuben; Kilumile, Menard; Mohamed, Fatma
Abstract: As the world is witnessing vast pollution during material production, construction and demolition processes of buildings there is a need to seek for alternative materials that will reduce the environmental impact. The present study borrows inspirations from termite's technique to create a material for constructing a naturally cemented mound structure. The studied termite mound was built from a mix of soil particles and termites saliva containing mucopolysaccharides and cellulase enzyme that digests cellulose into beta-glucose or shorter polysaccharides and oligosaccharides. These polysaccharides are found to be a source of soil stabilization and gluing property. In the process to mimic termites' activities clay bricks were produced from a mix of clay soil and cassava flour in a form of hot cassava paste as a source of polysaccharides at 1.5%, 3%, 4.5% and 6% weight of soil. Brick samples created presented an optimal value at 1.5% cassava flour with compressive strength higher than that of burnt clay bricks at 4.28 MPa .